2021
DOI: 10.2174/1574892816666210204125155
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between RNA Methylation Eraser FTO and Writer METTL3 in Renal Clear Cell Carcinoma Patient Survival

Abstract: Background: m6A-methyltransferaseMETTL3 anddemethylaseFTO regulate gene expressionby dynamically modifying RNAmethylation. However, theirclinical relevancein renal Clear Cell Carcinoma (CCRCC) hasnotbeenwell elucidated. Objective: This study aimsto investigate prognostic values of FTO and METTL3mRNA and DNA methylation, their differential expression andassociations with chemokines and inflammation-related genes in CCRCC. Method: Kaplan-Meier survival curves and multivariate cox regression were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…m6A modification is aberrant in various types of cancer and is associated with patient prognosis. The dysregulation of m6A modification also critically regulates malignant behaviors, such as proliferation, metastasis, tumor stemness, and drug resistance [ 50 53 ]. It has been reported that m6A modification regulators can function as either tumor promoters or tumor suppressors in different tumor types.…”
Section: Aberrant M6a Functions and Tumor Progressionmentioning
confidence: 99%
“…m6A modification is aberrant in various types of cancer and is associated with patient prognosis. The dysregulation of m6A modification also critically regulates malignant behaviors, such as proliferation, metastasis, tumor stemness, and drug resistance [ 50 53 ]. It has been reported that m6A modification regulators can function as either tumor promoters or tumor suppressors in different tumor types.…”
Section: Aberrant M6a Functions and Tumor Progressionmentioning
confidence: 99%
“…A potential role of m6A methylation in tumorigenesis and progression has been well documented [ 31 ]. Clear cell renal cell carcinoma (ccRCC) is the most common histological type of RCC, and several M6a-related genes have been shown to be associated with OS and/or DFS in ccRCC [ 32 34 ]. EIF3A is a highly conserved gene that may also be involved in the regulation of cellular, physiological, and pathological processes, not only in cancer [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more and more research has focused on the eld of the m6a interact on cancer [29].The potential role of m6A methylation in tumorigenesis and progression has been well documented [30].Clear cell renal cell carcinoma(ccRCC) is the most common histological type of RCC, and several M6a-related genes have been shown to be associated with OS and/or DFS in ccRCC [31][32][33].EIF3A is a highly conserved gene may also be involved in the regulation of cellular, physiological, and pathological processes not only in cancer [34].However,EIF3A,as a "reader", was hardly mentioned in ccRCC. The expression of EIF3A is different from that of other genes, which expresses at a low level in normal tissues, increases signi cantly in the presence of cancer, and decreases again in high grade tumors [34].Hence, we systematically investigated the prognostic signi cance of EIF3A in ccRCC.…”
Section: Discussionmentioning
confidence: 99%